Promoting Evidence-based Leadership Development: Designing and Evaluating Tourism and Hospitality Graduate Leadership Programs (Journal of Leadership, Accountability and Ethics, 2020)
Leadership development programs have become popular across higher education institutions globally, but research evidence about what does and does not work is yet to be sufficiently cultivated to support the effective development of leadership. Individual and collective leadership are two distinct forms of leadership that need to be integrated into the tourism and hospitality leadership program curriculum to solve current and future industry challenges. This conceptual paper presents an integrated framework that links leadership with an educational program-based model to generate evidence for continuous improvement. Assessment and evaluation strategies are proposed to guide leadership program evaluations and consequently leadership development. The paper also outlines areas for future research.
Keywords: Leadership; Accountability; Ethics; leadership development framework; tourism and hospitality; graduate leadership programs; evaluation